Tracking the Accidental Victim Using Andriod Application (International Journal of Emerging Trends in Science and Technology, 2016)
During disasters people face problems in communicating and informing about their location to their dearones and will be in need of urgent help Track the victim is an application that will solve the above problemThe application shall allow the user to select contacts to whom the location details must be sent, in case ofdisasters. The application shall track the location of the user. The application shall automatically send textand voice messages to preset contacts. The emergency call facility that is currently available will not allowthe user to send voice and text messages containing users location.This social issue is solved by our application. Even though emergency cal